Origin and evolution of intercrystalline brine in the northern Qaidam Basin based on hydrochemistry and stable isotopes - Ren, Qianhui; Li, Binkai; Zhang, Yan; Wu, Haitao (Frontiers in Environmental Science, 2023)
The Kunteyi Basin, located in northern Qaidam, is known as a significant potash ore deposit in China. It is of great significance to study the origin of the potassium-rich intercrystalline brine to support the exploitation of potassium salts. In this study, the major ion concentrations and isotopic ratios (δ2H, δ18O, and δ11B) of intercrystalline brine were used to analyze the evolution of the brine. The results show that the intercrystalline brine has a much higher concentration of total dissolved solids compared with the oil-field brine. Most of the ions are enriched except Ca2+ and Br−. The value of δ2H and δ18O are much negative while the δ11B values are positive. The analysis of CNa/CCl, CBr/CCl, Cl/(Na + K + Mg) and isotopes ratios, indicate that (1) Atmospheric precipitation is the primary source of water in brine; (2) The salinity of the brine is mainly influenced by halite dissolution; (3) The study area was influenced by the deep hydrothermal fluids. The thermal water recharged the Pleistocene layer, reacted with polyhalite, and formed Mg- and K-rich brine. The solution rose along the channel formed by the Shuangqiquan Fault and was supplied to the shallow intercrystalline brine.